2014
DOI: 10.2166/wst.2014.499
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of volatile organic compounds (VOCs) in surface water, soil, and groundwater within a chemical industry park in Eastern China

Abstract: This paper focuses on the distribution of volatile organic compounds (VOCs) in the surface water, soil, and groundwater within a chemical industry park in Eastern China. At least one VOC was detected in each of the 20 sampling sites, and the maximum number of VOCs detected in the surface water, groundwater, and soil were 13, 16, and 14, respectively. Two of the 10 VOCs with elevated concentrations detected in surface water, groundwater, and soil were chloroform and 1,2-dichloroethane. The characteristics of VO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 13 publications
1
5
3
Order By: Relevance
“…The most abundant VOC species was dichloromethane in the samples from the STP and the InCP and bromochloromethane in the samples from the OuCP. The results were different from the other research where chloroform was the compound with the highest concentration in the surface water from a chemical industrial park [ 22 ]. This indicated that the VOCs released by the chemical industrial processes directly affected the environment.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The most abundant VOC species was dichloromethane in the samples from the STP and the InCP and bromochloromethane in the samples from the OuCP. The results were different from the other research where chloroform was the compound with the highest concentration in the surface water from a chemical industrial park [ 22 ]. This indicated that the VOCs released by the chemical industrial processes directly affected the environment.…”
Section: Resultscontrasting
confidence: 99%
“…However, chemical industrial park’s industrial processes are not the only source of VOCs for samples collected outside a chemical industrial park. Benzene, toluene, ethylbenzene, and xylene (BTEX) have received much attention due to frequent detection in the environment, with the widespread use of petroleum products as their main source [ 22 , 23 ]. The BTEX concentration ranges in the InCP and the OuCP samples in the present study were ND–3.97 μg L −1 (mean: 1.50 μg L −1 ) and 1.00–3.55 μg L −1 (mean: 1.91 μg L −1 ), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…China (Liu et al, 2015) and a pesticide production site in Changzhou (Zhang et al, 2012) have also reported ranges in BTEXS levels consistent with the current study.…”
Section: Concentrations and Spatial Distributions Of Btexs In Surfacesupporting
confidence: 89%
“…Soil and groundwater contaminated by volatile organic compounds (VOCs) are suspected to have the carcinogenic risk and have caused a lot of public health issues [1,2]. The dynamic process of contaminants migrating through the unsaturated zone, entering into buildings located above, and threatening the health of human beings is called vapor intrusion (e.g., [3][4][5][6][7][8][9][10]).…”
Section: Introductionmentioning
confidence: 99%